Memahami Konsep Komponen Human Capital - Tahsya Riztia; Sefnie Chabita Wardhanie; Rony Edward Utama (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
In the increasingly digitized and complex work environment, human capital management has become a strategic determinant of organizational competitiveness. This study aims to develop and analyze an integrative conceptual framework comprising four core components of human capital—individual capability, individual motivation, workgroup effectiveness, and organizational climate—which collectively form a collaborative and adaptive managerial system. Employing a qualitative approach with an instrumental case study design, data were collected through in-depth interviews, participatory observations, and institutional document analysis involving 12 key informants from three institutions representing higher education, microfinance, and public bureaucracy sectors. Data were analyzed using thematic analysis based on Braun and Clarke’s six-phase framework, supported by NVivo 14 software to ensure transparency and accuracy in interpretation. The findings reveal that individual capabilities—such as agility, problem-solving, and digital literacy—are only effective when reinforced by intrinsic motivation, strong team synergy, and a supportive organizational climate. The integration of these four components demonstrably increases organizational productivity by up to 27% over two years and enhances resilience during crises. In conclusion, this study contributes to the theoretical development of human capital in the field of human resource management and offers practical guidance for organizations in designing responsive, adaptive, and sustainable HR strategies in the era of digital disruption.